Functional representation for the grand partition function of a multicomponent system of charged particles: Correlation functions of the reference system - Patsahan, O.V.; Mryglod, I.M. (Condensed Matter Physics, 2006)
Based on the method of collective variables (CV) with a reference system, the exact expression for the functional of the grand partition function of a m-component ionic model with charge and size asymmetry is found. Particular attention is paid to the nth particle correlation functions of the reference system which is presented as a m-component system of “colour” hard spheres of the same diameter. A two-component model is considered in more detail. In this case the recurrence formulas for the correlation functions are found. A general case of a m-component inhomogeneous system of the “colour” hard spheres is also analysed.